Integrating microbial source tracking with quantitative microbial risk assessment to evaluate site specific risk based thresholds at two South Florida beaches - Gitter, Anna; Gidley, Maribeth; Mena, Kristina D.; Ferguson, Alesia; Sinigalliano, Christopher; Bonacolta, Anthony; Solo-Gabriele, Helena (Frontiers in Microbiology, 2023)
Gitter conceived, designed, and conducted the QMRA analysis, analyzed data, prepared figures and/or table, authored and reviewed drafts of the paper, approved final draft, and is the corresponding author. Maribeth Gidley conceived, designed, and performed the experiments, contributed reagents/materials/analysis tools, analyzed data, prepared figures and/or tables, authored and reviewed drafts of paper, approved final draft, and serves as Principal Investigator. Kristina D. Mena assisted in the design of the QMRA analysis, contributed analysis tools, reviewed drafts of paper, and approved final draft. Alesia Ferguson was responsible for collection of video data and activity patterns assessments for the overall BEACHES project, reviewed and approved the final draft. Christopher Sinigalliano conceived, designed, and performed the experiments, oversaw, and coordinated all microbiological analysis and molecular microbial source tracking analysis, contributed reagents/materials/analysis tools, analyzed data, prepared figures and/or tables, authored and reviewed drafts of paper, and approved final draft. Anthony Bonacolta performed the experiments, reviewed drafts of the paper, and approved final draft. Helena Solo-Gabriele conceived and designed the experiments and the overall BEACHES project, oversaw the project, helped with field work, reviewed drafts of the paper, and approved final draft. She was also the Lead Principal Investigator for the overall BEACHES project.